2017
DOI: 10.1016/j.proci.2016.06.181
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustained catalytic combustion of carbon monoxide ignited by dielectric barrier discharge

Abstract: This paper presents the results of a study of self-sustained catalytic combustion of CO ignited by dielectric barrier discharge (DBD) using Ce 0.5 Zr 0.5 O y /TiO 2 (CeZr/Ti), CuZr 0.25 O y /TiO 2 (CuZr/Ti), and CuCe 0.75 Zr 0.25 O y /TiO 2 (CuCeZr/Ti) catalysts. DBD excites and dissociates some of the reactant molecules in the gas phase. These are more easily adsorbed on the catalyst surface than are ground-state species, therefore induction begins at a lower background temperature than in thermal catalysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Cu(NO 3 ) 2 ·3H 2 O, Ce(NO 3 ) 3 ·6H 2 O and Zr(NO 3 ) 4 ·5H 2 O were combined in a 4:3:1 M ratio and dissolved fully in 70 mL of ethanol at 80°C. This Cu:Ce:Zr ratio was selected on the basis of our previous study according to its good redox capability and oxygen storage capacity for CO oxidation [22,23]. Then, 0.24 mol/L of an oxalic acid solution was used as a pore former and was added quickly to the aforementioned nitrate solution with stirring to evaporate ethanol and to fully dissolve until a gel was formed at 80°C over nearly 6 h. After aging at room temperature for approximately 48 h, the gel was dried at 105°C for 12 h and then calcined in air at 550°C for 2 h.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Cu(NO 3 ) 2 ·3H 2 O, Ce(NO 3 ) 3 ·6H 2 O and Zr(NO 3 ) 4 ·5H 2 O were combined in a 4:3:1 M ratio and dissolved fully in 70 mL of ethanol at 80°C. This Cu:Ce:Zr ratio was selected on the basis of our previous study according to its good redox capability and oxygen storage capacity for CO oxidation [22,23]. Then, 0.24 mol/L of an oxalic acid solution was used as a pore former and was added quickly to the aforementioned nitrate solution with stirring to evaporate ethanol and to fully dissolve until a gel was formed at 80°C over nearly 6 h. After aging at room temperature for approximately 48 h, the gel was dried at 105°C for 12 h and then calcined in air at 550°C for 2 h.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Yang [2] and Scarpa [4] found that alkanes including methane, propane and n-octane could achieve self-sustained combustion successively over Pt-based catalyst supported ZSM-5 or γ-Al 2 O 3 with relatively lower concentration. In addition, the self-sustained combustion can be obtained by CO → CO 2 exothermic reaction over the CuCe/ZSM-5 and CuCe 0.75 Zr 0.25 /TiO 2 catalysts in our previous studies [5,6].…”
Section: Introductionmentioning
confidence: 81%
“…For instance, with discharge power increases from 25 to 42 W, toluene removal for CuCeZr/T increases from 98.2% to 100%, while the corresponding CO 2 selectivity increases from 64.8% to 94.2%. On the one hand, the background temperature further increases in the reactor through joule heating, dielectric loss, and gas heating in the plasma channel with the migration of electrons and ions [20], and it can activate the catalyst owing to the thermal chemistry. On the other hand, with the increase of input discharge power, plasma can activate catalyst gradually by changing the physicochemical properties of the catalyst, formation of hot spots, lowering the activation barrier and changing the reaction pathways, hence the catalyst's role becomes much more important or dominant.…”
Section: Toluene Removal By Dbd Coupling With Catalystmentioning
confidence: 99%